Anaplastic Thyroid Cancer: Clinical Picture of the Last Two Decades at a Single Oncology Referral Centre and Novel Therapeutic Options - Simões-Pereira, Joana; Capitão, Ricardo; Limbert, Edward; Leite, Valeriano (Cancers, 2019)
Anaplastic thyroid cancer (ATC) is a rare tumour but also one of the most lethal malignancies. Therapeutic modalities have usually been limited, but clinical trials with new drugs are now being implemented. The aims of this study were to analyse the clinical presentation, therapeutic modalities and independent prognostic factors for survival. We also reviewed the most recent literature on novel ATC therapies. We performed a retrospective analysis of 79 patients diagnosed between 2000 and 2018. Variables with impact on survival were identified using the Cox proportional-hazard regression model. At presentation, 6.3% had thyroid-confined disease, 30.4% evidenced extrathyroidal extension and 60.8% were already metastatic. Surgery was feasible in 41.8% and radiotherapy was applied to 35.4%, with those receiving >45 Gy having longer estimated survival (p = 0.020). Chemotherapy, either conventional or with tyrosine kinase inhibitors, was performed in 17.7% and 7.6%, respectively. Multimodality therapy with surgery, radiotherapy and chemotherapy/tyrosine kinase inhibitors (TKI) had the greatest impact on disease specific survival (DSS), providing a risk reduction of death of 96.9% (hazard ratio (HR) = 0.031, 0.005–0.210, p < 0.001). We concluded that most of these patients join reference centres at advanced stages of disease and multimodality treatment may offer the best chances for prolonging survival.